Novel Fuel Additives Chemical from Oil Palm Sap - Mohd Hasbi, Ab. Rahim (2016)
Production of new fuel additives chemical from abundant, cheap and biorenewable polyol. The catalytic process utilized green chemistry approach in which both the feedstock (polyol from oil palm sap) and solid catalytic material (red gypsum) originated from Malaysian industrial waste. The process is relatively simple and catalytic material can be reuse without regeneration process.